2017
DOI: 10.3390/molecules22071193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of the Degree of Processing of Radix Rehmanniae Preparata (Shu Dihuang) on Shu Dihuangtan Carbonization Preparation Technology

Abstract: Carbonization of Radix Rehmanniae Preparata (Shu Dihuangtan) via stir-frying could increase its homeostasis maintaining and antidiarrheal effects. To ensure these pharmacological functions, the quality of the raw material (processed Rehmanniae Radix) must be well controlled. Therefore, we analyzed the effects of different degrees of processing and adjuvants on processed Rehmanniae Radix (Shu Dihuang) by High Performance Liquid Chromatography (HPLC) chromatographic fingerprints, thermal gravimetric analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…It indicates that the DL characteristics became stable after the fourth processing cycle. This result is similar with previous chemical analyses which indicated that the chemical components were stable after the fifth processing cycle using plant metabolomics tools such as 1 HNMR and gas chromatography–mass spectrometry (GC–MS) [ 4 , 25 , 26 ]. Plant metabolomics provides a relatively comprehensive analysis of various compounds in biological systems based on specific platforms [ 30 ], and it has been considered as a suitable tool for herb quality control in a system level [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It indicates that the DL characteristics became stable after the fourth processing cycle. This result is similar with previous chemical analyses which indicated that the chemical components were stable after the fifth processing cycle using plant metabolomics tools such as 1 HNMR and gas chromatography–mass spectrometry (GC–MS) [ 4 , 25 , 26 ]. Plant metabolomics provides a relatively comprehensive analysis of various compounds in biological systems based on specific platforms [ 30 ], and it has been considered as a suitable tool for herb quality control in a system level [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies suggested that differences in chemical profiles of processed Rehmanniae radix became smaller after five processing cycles (Additional file 2 : Fig. S1) [ 4 , 25 , 26 ]. In this study, DL has been used to measure raw and processed Rehmanniae radix samples in order to investigate the processing approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical composition of RG is dominated by glycosides, mainly cyclic allene terpenoids, including leonuride, aucubin, catalpol, and rehmannioside A, B, C, and D; sugars, including D-glucose, D-galactose, D-fructose, and sucrose; and a variety of amino acids and inorganic elements. [105][106][107] RG has a wide range of clinical applications. It is currently reported that RG can be used to treat attention deficit hyperactivity disorder, 108 PD 109 , multiple sclerosis, 110 anxiety, 111 and memory disorders, 112 and it inhibits inflammatory responses 113,114 and has anti-fatigue activity.…”
Section: Rehmannia Glutinosa (Gaertn) DCmentioning
confidence: 99%